2014
DOI: 10.1111/jeb.12451
|View full text |Cite
|
Sign up to set email alerts
|

Positive effect of the yellow morph on female reproductive success in the flower colour polymorphic Iris lutescens (Iridaceae), a deceptive species

Abstract: The deceptive Iris lutescens (Iridaceae) shows a heritable and striking flower colour polymorphism, with both yellow-and purple-flowered individuals growing sympatrically. Deceptive species with flower colour polymorphism are mainly described in the family Orchidaceae and rarely found in other families. To explain the maintenance of flower colour polymorphism in I. lutescens, we investigated female reproductive success in natural populations of southern France, at both population and local scales (within popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 51 publications
(79 reference statements)
1
14
1
Order By: Relevance
“…The strong pollinator limitation on flowers of both I. lutescens and I. pumila, and the absence of surrounding flower choice (Imbert et al 2014a) are consistent with exploiting the naivety of recently emerged pollinators, as reported in some deceptive orchids (Jersáková et al 2006b, Dormont et al 2010b. Some examples of pollinator-mediated selection have been reported in plant species visited by a low diversity of pollinators (Sletvold et al 2016).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…The strong pollinator limitation on flowers of both I. lutescens and I. pumila, and the absence of surrounding flower choice (Imbert et al 2014a) are consistent with exploiting the naivety of recently emerged pollinators, as reported in some deceptive orchids (Jersáková et al 2006b, Dormont et al 2010b. Some examples of pollinator-mediated selection have been reported in plant species visited by a low diversity of pollinators (Sletvold et al 2016).…”
Section: Discussionsupporting
confidence: 58%
“…Pollinators learn to avoid the deceptive flower morphs and visit the alternative ones, generating negative frequency-dependent selection (Gigord et al 2001, Kagawa andTakimoto 2016). However, experiments in natural populations have failed to detect this mechanism in various species (see discussion in Imbert et al 2014a).…”
Section: Researchmentioning
confidence: 99%
“…This distribution pattern is very rare in natural color polymorphic populations. Studies have shown that intraspecific flower color variation is often attributed to genetic drift, pollination-mediated selection, environmental conditions, or herbivory [13,[29][30][31]. In our experiments, the populations grow across a small range, with the whole population occurring on similar rocks and exposed to the same climatic conditions.…”
Section: Discussionmentioning
confidence: 95%
“…250 entomophilous species that inhabit the Earth's North Temperate Zone (Mathew, 1981). Iris flowers have elaborate and versatile pollinator attractants, including different color patterns of tepals and sepals with specific orientation and distinctive nectar guides, floral odors, nutritive nectars and pollen, as well as non-nutritive forms of reward, such as shelter and thermal energy (Sapir et al, 2006;Vereecken et al, 2013;Imbert et al, 2014;Guo, 2015;Pellegrino, 2015). Regarding pollen chemistry, triglycerides are the primary nutrient reserve in Iris pollen since the grains are starchless (Franchi et al, 1996).…”
Section: Comparative Assessment Of Ft-raman and Ftir: A Case Study Onmentioning
confidence: 99%